1999
DOI: 10.1192/bjp.175.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy or imaginal exposure in the treatment of post-traumatic stress disorder

Abstract: Clinical benefits for exposure or cognitive therapy were maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 13 publications
2
59
0
3
Order By: Relevance
“…Regardless of the chosen treatment technique, about 40% of subjects present a recurrence of symptoms within the year (Martenyi & Soldatenkova, 2006, Tarrier, Sommerfeld, Pilgrim, & Humphreys, 1999) with a risk of relapse estimated at 20% within five years (Boe, Holgersen, & Holen, 2010). Most studies found a weak association of pre-trauma factors with recovery, presumably due to the strong influence of post-trauma factors (Rosellini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the chosen treatment technique, about 40% of subjects present a recurrence of symptoms within the year (Martenyi & Soldatenkova, 2006, Tarrier, Sommerfeld, Pilgrim, & Humphreys, 1999) with a risk of relapse estimated at 20% within five years (Boe, Holgersen, & Holen, 2010). Most studies found a weak association of pre-trauma factors with recovery, presumably due to the strong influence of post-trauma factors (Rosellini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently investigated forms of treatment in these long-term follow-up studies have included imaginal exposure-based treatments such as that used by Tarrier and colleagues 49 and Power and colleagues, 50 while other studies have included combinations of imaginal plus in vivo techniques as used by Richards and colleagues, 48 Foa and colleagues 52 and Bisson and colleagues. 51 Other forms of exposure-based treatments have included trauma-focused group therapy which provides patients with opportunities for exposure to their own traumatic events in addition to vicarious exposure to traumatic events experienced by other group members.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…With regard to patient characteristics the populations vary greatly. Of the six studies listed, three included adult civilians of both genders who had developed PTSD following trauma such as accident or assault, [48][49][50] one study included male and female patients who had attended accident and emergency facilities following physical injury, 51 one study included females only who had been victims of assault, primarily sexual assault, 52 and the remaining study included Vietnam veterans. 53 Among these studies the sample size varied considerably, ranging from as small as seven 48 up to 180.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…In addition, those with more general apprehensions may raise concerns about how such guidelines will be used and their potentially stifling impact on research efforts to design and support even more effective treatments. This latter point is especially important given that a considerable number of individuals with PTSD still fail to respond to the most empirically efficacious treatments available at present (Andrews et al, 2002;Tarrier, Sommerfield, Pilgrim, & Humphreys, 1999).…”
Section: The First Is the Clinical Resource Efficiency Support Team (mentioning
confidence: 98%